The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ijn.s283981
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cinnamaldehyde and Doxorubicin Co-Loaded Graphene Oxide Wrapped Mesoporous Silica Nanoparticles for Enhanced MCF-7 Cell Apoptosis</p>

Abstract: Background Combined chemotherapy is often affected by the different physicochemical properties of chemotherapeutic drugs, which should be improved by the reasonable design of co-loaded preparations. Purpose A kind of simple but practical graphene oxide (GO) wrapped mesoporous silica nanoparticles (MSN) modified with hyaluronic acid (MSN@GO-HA) were developed for the co-delivery of cinnamaldehyde (CA) and doxorubicin (DOX), in order to enhance their combined treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Zhao et al suggested that CA encapsulated in submicrometer emulsions exhibited higher plasma concentration, faster tissue distribution, and better antitumor effects in rats when compared to CA alone [ 32 ]. Similarly, Dong et al reported that nanogel packaging of CA enabled the controlled release and oxidation inhibition of drug and oxidation inhibition, which consequently increased CA's bioavailability and more effectively promoted cancer cell apoptosis [ 53 ]. With the advancement in molecular biology, a large number of bioactive substances, including dextran, silica, chitosan, cyclodextrin, and hyaluronic acid, have been found to synthesize carriers for improving the therapeutic efficacy of CA [ 46 , 48 , 51 , 53 , 60 ].…”
Section: Progress In the Pharmacological Characteristics Of Camentioning
confidence: 99%
“…Zhao et al suggested that CA encapsulated in submicrometer emulsions exhibited higher plasma concentration, faster tissue distribution, and better antitumor effects in rats when compared to CA alone [ 32 ]. Similarly, Dong et al reported that nanogel packaging of CA enabled the controlled release and oxidation inhibition of drug and oxidation inhibition, which consequently increased CA's bioavailability and more effectively promoted cancer cell apoptosis [ 53 ]. With the advancement in molecular biology, a large number of bioactive substances, including dextran, silica, chitosan, cyclodextrin, and hyaluronic acid, have been found to synthesize carriers for improving the therapeutic efficacy of CA [ 46 , 48 , 51 , 53 , 60 ].…”
Section: Progress In the Pharmacological Characteristics Of Camentioning
confidence: 99%
“…Dong et al. ( 2020 ) developed mesoporous silica nanoparticles ( Figure 6 ) coated with graphene oxide modified by HA for the combined administration of CA and DOX to enhance their combined therapeutic effect on tumor cells. CA and DOX co-loaded graphene oxide coated mesoporous silica nanoparticles (MSNCA @ GODOX-HA) actively targeted tumor cells through the “ligand receptor” affinity between HA and CD44 receptors, improved the advantages of CA and DOX, limited their shortcomings, so as to achieve effective treatment of cancer.…”
Section: Types and Characteristics Of Ndcdsmentioning
confidence: 99%
“…DOX was employed as the fluorescent probe as it emits red fluorescence under a specified wavelength of excitation light. 41,42 The cell nuclei were stained in blue by DAPI since it is a fluorescent dye that binds strongly to DNA. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%